Identifikasi Penyakit pada Daun Jambu Kristal Berbasis Android dengan Metode Enterprise Unified Process - Ari Kurniawan Sudiarto; Khoirida Aelani; Fresa Dwi Juniar (LPPM STMIK AMIK BANDUNG, 2020)
Subang Crystal Guava farmer groups have problems in the management and maintenance of plants that are still carried out by way of going down outside the Operating System Procedure (SOP) provided by the Subang Agriculture Service, especially in the management of disease prevention or plant pests and harvesting of Crystal Guava fruit . This makes the process of checking yields take a long time if it has to be adjusted to the SOP provisions. One alternative solution that aims to provide direction and treatment to farmers in managing guava crystals is to apply informatics technology in the form of an application model built for disease identification on Android-based guava leaves. This application uses the camera facilities on mobile phones to take photos of guava leaf samples. The research method used is a software development method (Enterprise Unified Process) whose stages include Construction, Transition, and Production. Java as a programming language, and Android Studio Tools as the editor. Application Identification of diseases on the guava leaves that were built after the trial can be used by the Crystal Guava Farmers in the Subang farmer group as a tool to determine the disease in the guava plants so that a method is obtained to treat the guava plants with a yield that is harvested. expected to be optimal